If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(c + -5) = c + -2 Reorder the terms: 2(-5 + c) = c + -2 (-5 * 2 + c * 2) = c + -2 (-10 + 2c) = c + -2 Reorder the terms: -10 + 2c = -2 + c Solving -10 + 2c = -2 + c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-1c' to each side of the equation. -10 + 2c + -1c = -2 + c + -1c Combine like terms: 2c + -1c = 1c -10 + 1c = -2 + c + -1c Combine like terms: c + -1c = 0 -10 + 1c = -2 + 0 -10 + 1c = -2 Add '10' to each side of the equation. -10 + 10 + 1c = -2 + 10 Combine like terms: -10 + 10 = 0 0 + 1c = -2 + 10 1c = -2 + 10 Combine like terms: -2 + 10 = 8 1c = 8 Divide each side by '1'. c = 8 Simplifying c = 8
| -7+N=-12 | | 4*(7+3x)=32 | | 1x-4y=5 | | x+x^2=21 | | -2(-3-t)=10 | | 3x-4=5x-3 | | 4x=4x-20 | | x(2x-5)=493 | | 25=4v+17 | | 4a=7b | | f(x)=-4ln(6x) | | 2(2x+3x)=1+2 | | 44x-29=3x-15 | | x(2x-4)=665 | | 5x+3y=105 | | 10*2-5*2=x | | (4x-7)(6x+9)= | | x(2x-4)=286 | | 4[6x-4(y-1)]= | | 11+123=x | | 8(m-2)=3 | | 5x+7y+35=0 | | 83=5v+8 | | 3x-13=38 | | 3(5y-6)-4(y-3)= | | sqrt(8x+17)-2x=3 | | (2x+5)+(2x-23)=90 | | .6x+-1.3=x | | 3cotx=5 | | 3(4r-7)-4(r-1)= | | ln(x^2-3x)=0 | | (3x+35)+(5x-15)=180 |